A Comparative Assessment of Vegetation Diversity Under Coffee Plantations Inside and Outside Protected Forest Areas - Ifran Imanda; Sabaruddin Kadir; M. Umar Harun; Wijaya Mardiansyah (Program Pascasarjana Universitas Sriwijaya, 2022)
The existence of tree vegetation planted in coffee plantations as shade trees is believed to have a positive influence on the growth and production of coffee plants. This study aims to analyze the diversity of coffee plant vegetation in three age classes planted inside and outside protected forest areas included in the administrative area of North Dempo and Central Dempo Districts, Pagar Alam City, South Sumatra Province. The results of observations and calculations of Value IVI found that Albizia sumatrana was the dominant species in all coffee plantations at various age levels. The IVI values of Albazia Sumatrana in coffee plants aged < 5 years were 157.32 (inside PF) and 720.92 (outside PF), in coffee plants aged < 10 years, were 84.30 (inside PF) and 155.51 (outside PF), while in coffee aged > 10 years is 75.46 (inside PF) and 95.92 (outside PF). Assessment using the Shanon Index and Simpon Index showed the same results; coffee plantations at all age levels had a moderate diversity index, except for vegetation in coffee plantations aged < 5 years which were outside protected forest areas and had low diversity index values. Through the availability of this information, it is hoped that it will be used as initial information for selecting vegetation types that will be used to support restoration activities in areas around protected forests.